The German health care system: understanding and accessing health care in Germany - Obermann, Konrad; Müller, Peter; Zilch, Sebastian; Winter, Christian Martin; Glazinski, Bernd (medhochzwei, 2021)
Germany's health care system takes care of around 82 million people and is built on the principles of solidarityand equity. At the same time, it is a large and attractive market. It's long history and ever more detailed regulation,however, make it difficult to understand the system and to enter the market.The recent Corona crisis has shown hat the German health care system is robust, resilient, and flexible to cope evenwith unprecedented situations.This book, written by scientists and practitioners from different professional backgrounds, is intended to providea swift, yet comprehensive, up-to-date, and authoritative introduction into how health care is delivered, financed,and governed in Germany.We have included all major changes and reforms up until September 2020.
Literaturverzeichnis: Seite 298
Keywords: Aufsatzsammlung; Krankenversicherung; Finanzierung; Gesundheitswesen; Deutschland